Models Of Language Innovation and Creativity for Students Early Childhood Education Programs - Kurniawan, Heru; Fakhrudin, Asef Umar (KLITIKA Jurnal Ilmiah Pendidikan Bahasa dan Sastra Indonesia, 2023)
One of the educational materials for early childhood education is language. Language in early childhood education must be able to innovate and be created into creative works for early childhood. This study aims to explain the role of the early childhood education community in innovating and creating language into creative works for early childhood education. The research conducted was field research in early childhood education study programs. Data collection techniques were carried out by interviews, documentation, and observation. While data analysis is done by data reduction, data classification, and data verification. The results of his research are language innovation and creativity in early childhood education study programs carried out through:(1) language writings that focus on creating and innovating early childhood education ideas into writings aimed at early childhood education;(2) visual language works that create and innovate ideas into visual language works in the form of activity books;(3) musical language works that innovate and create music with language so as to produce music for early childhood education;(4) fairy tale language works that innovate and create language into spoken and written fairy tales or fairy tale books for early childhood; and (5) cinema language works that innovate and create ideas into cinema products for early childhood education.